Hubungan Riwayat Pemberian ASI Eksklusif terhadap Kejadian Stunting Balita 25-59 Bulan di Wilayah Kerja Puskesmas Dolok Masihul Kabupaten Serdang Bedagai - Ayu Rizkya Damanik; Reni Agustina Harahap (Universitas Batanghari Jambi, 2023)
Stunting is an outcome of nutritional status that occurs when a child has a height or length of less than -2.0 standard deviation (SD) compared to the population average. The nutritional status of stunting is calculated by comparing the height or length according to the age of the toddler, according to the World Health Organization (WHO) z-score chart (WHO, 2018). One of the causes of stunting in toddlers is not being given exclusive breastfeeding during the first 0-6 months of age because breast milk is needed during the baby's growth period so that their nutritional needs are fulfilled. The purpose of this study was to find out the relationship between the history of exclusive breastfeeding and the incidence of stunting in toddlers in the working area of the Dolok Masihul Health Center, Serdang Bedagai Regency. The type of research used is an observational research design with a cross-sectional study approach, where the dependent and independent variable data are observed and measured at the same time. There were 31 respondents who were parents and also stunted and non-stunted toddlers. The results of the study were obtained using chi-square tests between the variable history of exclusive breastfeeding on the incidence of stunting and the variable the first time a child was given food/drink other than breast milk on the incidence of stunting, the p value = 0.00 was then compared with the value a = 0.05 so that p value <a (0.00 <0.05)Â meaning that there is a relationship between history of exclusive breastfeeding and the incidence of stunting and there is a relationship the first time a child is given food/drink other than breast milk to the incidence of stunting in the working area of the Dolok Masihul Health Center, Serdang Bedagai Regency .